Students' Perception of the Outside Java Students' Association (IKMALJA) Kudus Towards the Giving of Zakat Fitrah for Students as Mustahiq (LP2M IAIN kUDUS, 2025)
Not all students have the same understanding of the meaning of the eight asnaf who are entitled to receive zakat in the Quran, Surah At Taubah, verse 60. For students who are members of the Out-of-Java Student Association (IKMALJA) Kudus, they are not a priority recipient of zakat, especially zakat fitrah. Although they have the right as fi sabilillah (people who fight in the way of Allah) to receive zakat. This study aims to determine and discuss the perceptions of students who are members of the Out-of-Java Student Association (IKMALJA) Kudus regarding the provision of zakat fitrah for students as mustahiq. The research approach used is qualitative with a descriptive-sociological nature. This type of research is fieldwork. Data were collected through unstructured interviews, documents, and literature. The results of the study showed that the majority of students who are members of IKMALJA Kudus do not fully understand the mustahiq of zakat fitrah. The perception of IKMALJA Kudus students regarding mustahiq zakat is that they do not feel part of the recipients of zakat fitrah. They assume that zakat fitrah is only given to people who are categorized as poor and needy.